Masora und Exegese Untersuchungen zur Masora und Bibeltextüberlieferung im Kommentar des R. Schlomo ben Yitzchaq (Raschi) - Joe Petzold, Kay (Materiale Textkulturen, 2019)
The commentary of Rashi (Rabbi Shlomo ben Yitzhak, b. Troyes 1040, d. 1105), part of the Jewish core curriculum, is reprinted here together with the Hebrew biblical text. This study takes selected portions to investigate citations of the Hebrew bible and the Masorah in Rashi's commentary, thus providing an introduction to medieval Jewish biblical interpretation and the Ashkenazi tradition of reading the Hebrew bible.